Effects of music on post-stroke sleep disorders and treatment perspectives: review and narrative synthesis - Yang, Shuangying; Yan, Xue; Zhang, Ziwu; Gao, Wanning; Zhang, Tengyue; Zhang, Weimin (Frontiers in Human Neuroscience, 2026)
IntroductionSleep disorders represent the most prevalent psychiatric complication following stroke, seriously impacting patients' neurological recovery, functional prognosis, and quality of life. Music therapy, as a safe, cost-effective, and non-invasive intervention, is widely employed to ameliorate post-stroke sleep disorders. However, the precise mechanisms underlying music therapy's effects on post-stroke sleep disorders require further elucidation. This review aims to systematically examine the efficacy of music therapy for post-stroke sleep disorders and to elucidate the underlying physiological mechanisms through which music may improve sleep outcomes in this population.MethodsWe conducted a systematic search across the Cochrane Library, PubMed, Embase, Web of Science, China National Knowledge Infrastructure (CNKI), Wanfang Data, and VIP, with a search time frame ending in August 2025. Quality assessment was performed using the Version 2 of the Cochrane risk-of-bias tool for randomized trials (RoB 2).ResultsA total of 1,363 subjects from 14 original articles met the criteria for inclusion in the systematic review. Each study has shown that music intervention can effectively improve the sleep status in patients with post-stroke sleep disorders.